2016
DOI: 10.1111/adb.12474
|View full text |Cite
|
Sign up to set email alerts
|

Craving behavioral intervention for internet gaming disorder: remediation of functional connectivity of the ventral striatum

Abstract: Psychobehavioral intervention is an effective treatment of Internet addiction, including Internet gaming disorder (IGD). However, the neural mechanisms underlying its efficacy remain unclear. Cortical-ventral striatum (VS) circuitry is a common target of psychobehavioral interventions in drug addiction, and cortical-VS dysfunction has been reported in IGD; hence, the primary aim of the study was to investigate how the VS circuitry responds to psychobehavioral interventions in IGD. In a cross-sectional study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 64 publications
(89 reference statements)
3
40
0
Order By: Relevance
“…As shown in Table 1, IGD and HC participants were well-matched for age, smoking status, and alcohol use. Consistent with prior work in different cohorts (Zhang et al, 2016b(Zhang et al, , 2016cLiu et al, 2017), and with the findings from DUDs, IGD participants scored significantly higher on self-report indices of impulsivity (Patton et al, 1995), depression (Beck et al, 1996), and anxiety (Beck et al, 1988) (p'so0.005; details in Table 1).…”
Section: Participantssupporting
confidence: 85%
See 1 more Smart Citation
“…As shown in Table 1, IGD and HC participants were well-matched for age, smoking status, and alcohol use. Consistent with prior work in different cohorts (Zhang et al, 2016b(Zhang et al, , 2016cLiu et al, 2017), and with the findings from DUDs, IGD participants scored significantly higher on self-report indices of impulsivity (Patton et al, 1995), depression (Beck et al, 1996), and anxiety (Beck et al, 1988) (p'so0.005; details in Table 1).…”
Section: Participantssupporting
confidence: 85%
“…Thus, while the clinical significance of our findings requires further investigation, these data also the possibility that interventions specifically aimed at increasing engagement of limbic reward regions involved in salience encoding, eg, contingency management (Yip et al, 2015;Garrison et al, 2017), might be helpful in reducing Internet addiction severity in youth with IGD. In contrast, recent data suggest that behavioral interventions for IGD may partially operate via a reduction of resting state striatal functional connectivity (Zhang et al, 2016b). Thus, while further work extending treatment-related findings to cingulo-parietal IC dorsomedial frontal IC dorsolateral frontal IC Figure 3 Dorsal inhibitory control networks.…”
Section: Discussionmentioning
confidence: 96%
“…Bx = behavior; CBT = Cognitive Behavioral Therapy; CIAS = Chinese Internet Addiction Scale; DF = Dungeon & Fighter; GASA = Gaming Addiction Scale for Adolescents; IAS = Internet Addiction Scale; MMORPG = Massive Multiplayer Online Role-Playing Games; OGCAS = Online Game Cognitive Addiction Scale; PVP = Problem Video Game Playing Scale; RCT = randomized control trial; tx = treatment; YIAS = Young Internet Addiction Scale * a sample of healthy controls was recruited by not included in primary analyses; ** all participants had a diagnosis of attention deficit hyperactivity disorder; *** all participants had a diagnosis of major depressive disorder; † participants were randomly assigned to the two medication groups but the control group were participants who declined medication treatment (not randomly assigned). †† similar results were presented in two other publications by the same authors; the paper that presented on the largest sample size was chosen for inclusion (Zhang, Ma, et al, 2016; Zhang, 2016a). …”
Section: Figurementioning
confidence: 63%
“… †† similar results were presented in two other publications by the same authors; the paper that presented on the largest sample size was chosen for inclusion (Zhang, Ma, et al, 2016; Zhang, 2016a). …”
Section: Figurementioning
confidence: 63%
“…Furthermore, previous studies showed that behavioral interventions are effective in ameliorating both addiction severity [ 32 , 33 ] and depression symptoms in individuals with IGD or IA in general [ 34 36 ]. Examining how behavioral interventions influence emotional network connectivity and its associations with reduction in depression and addiction symptoms would provide additional evidence in support of shared neural substrates of IGD and depression.…”
Section: Introductionmentioning
confidence: 99%